Tapping linked to function and structure in premanifest and symptomatic Huntington disease [Image: see text] - Bechtel, N. (American Academy of Neurology, 2010)
OBJECTIVE: Motor signs are functionally disabling features of Huntington disease. Characteristic motor signs define disease manifestation. Their severity and onset are assessed by the Total Motor Score of the Unified Huntington's Disease Rating Scale, a categorical scale limited by interrater variability and insensitivity in premanifest subjects. More objective, reliable, and precise measures are needed which permit clinical trials in premanifest populations. We hypothesized that motor deficits can be objectively quantified by force-transducer-based tapping and correlate with disease burden and brain atrophy. METHODS: A total of 123 controls, 120 premanifest, and 123 early symptomatic gene carriers performed a speeded and a metronome tapping task in the multicenter study TRACK-HD. Total Motor Score, CAG repeat length, and MRIs were obtained. The premanifest group was subdivided into A and B, based on the proximity to estimated disease onset, the manifest group into stages 1 and 2, according to their Total Functional Capacity scores. Analyses were performed centrally and blinded. RESULTS: Tapping variability distinguished between all groups and subgroups in both tasks and correlated with 1) disease burden, 2) clinical motor phenotype, 3) gray and white matter atrophy, and 4) cortical thinning. Speeded tapping was more sensitive to the detection of early changes. CONCLUSION: Tapping deficits are evident throughout manifest and premanifest stages. Deficits are more pronounced in later stages and correlate with clinical scores as well as regional brain atrophy, which implies a link between structure and function. The ability to track motor phenotype progression with force-transducer-based tapping measures will be tested prospectively in the TRACK-HD study. GLOSSARY: CoV: = coefficient of variation; DBS: = disease burden score; Freq: = frequency; HD: = Huntington disease; ICV: = intracranial volume; IOI: = interonset interval; ΔIOI: = deviation from interonset interval; IPI: = interpeak interval; ΔIPI: = deviation from interpeak interval; ITI: = intertap interval; log: = logarithmic; MT: = metronome tapping; ΔMTI: = deviation from midtap interval; preHD: = premanifest Huntington disease; RT: = reaction time; ST: = speeded tapping; TD: = tap duration; TF: = tapping force; TFC: = Total Functional Capacity; UHDRS: = Unified Huntington's Disease Rating Scale; UHDRS-TMS: = Unified Huntington's Disease Rating Scale-Total Motor Score; VBM: = voxel-based morphometry.